Analisis perilaku kepemimpinan guru Indonesia di era pandemi Covid 19 menggunakan Rasch - Donna Sampaleng; Yuyun Elizabeth Patras; Baharuddin Baharuddin; Rais Hidayat (Jurnal Konseling dan Pendidikan)
Valid and reliable information regarding teacher leadership behavior in the era of the COVID-19 pandemic is very important. This study aims to find a reliable research instrument on teacher leadership in the era of the COVID-19 pandemic and at the same time recommend important findings for improving teacher leadership behavior. The study began with a theoretical study to obtain content validity, continued with expert validity, readability trials, and finally distributed the instrument via online. Analysis of research data using the Rasch model with 6 tests. The research data comes from 1200 teachers in Indonesia. The findings are: (1) recommended 10 items of instruments for research on teacher leadership behavior in the era of the covid 19 pandemic, (2) recommended 4 important findings to improve the condition of teacher leadership behavior, namely: (i) reflection skill, (ii) collaboration and communication, (iii) learning technology, and (iv) learning community.